Geraniol-Loaded Polymeric Nanoparticles Inhibit Enteric Pathogens on Spinach during Posttreatment Refrigerated and Temperature Abuse Storage - Perez-Lewis, Keila L.; Yegin, Yagmur; Cisneros-Zevallos, Luis; Castillo, Alejandro; Kerth, Chris R.; Akbulut, Mustafa; Taylor, Thomas Matthew (Frontiers in Sustainable Food Systems, 2018)
Postharvest cross-contamination of produce with bacterial human pathogens reduces the usefulness of produce as a source of wholesome human food. The application of nanoencapsulated natural antimicrobials, including essential oil components of plants, can help protect produce safety by decontaminating produce from microbial pathogens. The primary objective of this research was to determine the efficacy of antimicrobial interventions on pathogen-inoculated spinach samples stored refrigerated (5°C) for up to 10 days, or refrigerated (5°C) for 5 days with subsequent moderate (15°C) or severe (25°C) temperature abuse thereafter until a total of 10 days had elapsed. The secondary objective of the study was to determine the capacity of antimicrobial interventions to inhibit and/or reduce pathogen numbers on spinach when inoculation followed intervention treatment, simulating cross-contamination of spinach following postharvest sanitizing of spinach. Rinsed spinach was portioned into samples and inoculated with cocktailed antibiotic-resistant pathogens to 6.1 ± 0.1 log10 CFU/cm2 for each pathogen. Treatments of geraniol-loaded polymeric nanoparticles (0.5 wt.% geraniol), unencapsulated geraniol (0.5 wt.%), and 200 ppm free and available chlorine (FAC; pH 7.0) were applied to pathogens-inoculated or non-inoculated spinach samples. Following treatment, samples were collected for determining pathogen survival or were covered and held to determine changes in microbial populations (inoculated pathogens and naturally contaminating microbial hygiene indicators) during posttreatment simulated refrigerated and/or temperature-abuse storage. Changes in pathogen numbers were assessed periodically over 10 days for refrigerated (5°C), moderately (15°C), or severely (25°C) temperature-abused spinach. Immediately following treatment by FAC, unencapsulated or nanoparticle-entrapped geraniol, Escherichia coli O157:H7 and Salmonella counts on spinach ranged from 1.5 to 6.1 log10 CFU/cm2. Geraniol-loaded nanoparticles reduced pathogens to non-detectable numbers (detection limit: 0.5 log10 CFU/cm2) on refrigerated and moderately temperature-abused samples (15°C) within 7 days of storage posttreatment, and after 10 days of severe thermo-abuse storage (25°C). Conversely, FAC treatment did not reduce pathogens to non-detectable numbers for refrigerated spinach, and was not observed to inhibit pathogen growth in temperature-abused samples. Application of encapsulated geraniol can reduce pathogens on spinach surfaces, preventing their transmission to consumers, aiding the retention of produce wholesomeness, and utility for human consumption and nutrition.